2018
DOI: 10.3390/foods7080128
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Pancreatin-Induced Digestion of Starch in Starch Granules by Starch/Fatty Acid and Starch/Flavonoid Complexes in Retrograding Rice Flour

Abstract: Adzuki beans are used to prepare foods with glutinous and non-glutinous rice in Japan, and adzuki bean pigments are able to color rice starch a purplish red. This study deals with the adzuki bean extract-dependent suppression of starch digestion of non-glutinous rice flour (joshinko in Japanese), which was gelatinized in boiling water and then cooled to 37 °C. Accompanying the treatment of joshinko with pancreatin, amylose and amylopectin were released from the joshinko particles, and the released amylose and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…On the other hand, it has been reported that extrusion caused the formation of amylose-lipid complex and its supramolecular structure and then retained the crystallinity structure, which decreased the degree of gelatinization ( 15 , 34 ). Moreover, in contrast to ME, the instant powder obtained with IE possessed a higher flavonoids content ( Table 2 ) that can more effectively prevent the development of starch-iodine complex, decreasing the DG value ( 35 ). Therefore, the difference of DG between IE80 and ME80 could be influenced by these two factors.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it has been reported that extrusion caused the formation of amylose-lipid complex and its supramolecular structure and then retained the crystallinity structure, which decreased the degree of gelatinization ( 15 , 34 ). Moreover, in contrast to ME, the instant powder obtained with IE possessed a higher flavonoids content ( Table 2 ) that can more effectively prevent the development of starch-iodine complex, decreasing the DG value ( 35 ). Therefore, the difference of DG between IE80 and ME80 could be influenced by these two factors.…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, adzuki beans are cooked with rice in the East Asia region. The flavonoids from the adzuki bean, such as quercetin and vignacyanidin, could interact with rice starch to form hydrophobic starch/flavonoid complexes, resulting in the suppression of pancreatin‐induced digestion (Hirota & Takahama, 2018). In addition, the colored rice was digested more slowly in vitro than the normal rice, probably owing to the covalent bond between rice and procyanidins and their oxidation products formed during cooking (Takahama et al., 2019).…”
Section: Processing Of Adzuki Bean and Its Componentsmentioning
confidence: 99%